The economic laws of scientific research - Kealey, Terence (Basingstoke [England] : Macmillan ; New York : St. Martin's Press, 1996)
During the 1980s Terence Kealey was universally derided for his claims that British and American science were expanding fast. Everyone else thought that they were in decline. He has been vindicated, but he had an unfair advantage; he knew the economic laws of scientific research and his critics did not. This book now makes them available to all. If state-funded research promotes economic, cultural or even scientific growth, why do Japan and Switzerland flourish in its near-absence while Russia and India have stagnated in a sea of government largesse? Why has Britain's relative economic decline, and that of America, coincided with their government's funding of research? Assessing the evidence from international comparisons and historical research, Terence Kealey shows how the free market approach has proved by far the most successful in promoting science, innovation, wealth and happiness.
1. Francis Bacon and Adam Smith -- 2. Research and Development in Antiquity -- 3. The So-called Dark Ages -- 4. The Commercial Revolution -- 5. The Agricultural Revolution -- 6. The Industrial Revolution -- 7. Economic History since 1870 -- 8. Science Policies of the Twentieth Century -- 9. The Economics of Research: Why the Linear Model Fails -- 10. The Real Economics of Research -- 11. The So-called Decline of British and American Science -- 12. Dr Pangloss was Right.
Includes bibliographical references (p. 354-368) and index.
Keywords: Research, Industrial -- Economic aspects -- History; Science -- History; Economic history